Preparation process of wear-resistant shirt
By using wear-resistant finishing liquid and specific process treatment, the problem of traditional shirt fabrics being easily worn after long-term wear or frequent washing is solved, achieving high wear-resistant and washable effects, while maintaining the breathability and comfort of the fabric .
Patent Information
- Application Number
- CN202411769942.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional shirt fabrics are prone to wear and pilling problems after long-term wear or frequent washing, which affects the durability and wearing experience of the shirt.
A wear-resistant finishing solution is adopted, including polyurethane wear-resistant agent, penetrant JFC, modified magnesium powder, modified sodium lignin sulfonate and modified aerogel. Through the plunging and baking process, the finishing solution is uniform. Permeate into the inside of the fabric to form a stable wear-resistant layer.
It significantly improves the wear and wash resistance of the shirt, while maintaining the breathability and comfort of the fabric, extending the service life of the shirt.
Smart Images

Figure CN119433992A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of textile processing, and in particular relates to a preparation process of a wear-resistant shirt. Background Art
[0002] As an important part of daily clothing, the durability and comfort of shirts have always been the focus of consumers. However, traditional shirt fabrics are often prone to wear and pilling after long-term wear or frequent washing, which affects the appearance and wearing experience of the shirts. Therefore, it is particularly important to develop a process method that can effectively improve the wear resistance of shirts. Summary of the invention
[0003] The present invention provides a preparation process of a wear-resistant shirt, aiming to solve the above-mentioned problem.
[0004] The present invention is achieved by a process for preparing a wear-resistant shirt, comprising the following steps: S1 selects shirt fabrics that are breathable and comfortable to wear, and pre-shrunk the fabrics; S2 performs cutting, piece inspection, gluing, sewing and ironing to produce finished shirts; S3 washes and pre-treats the shirts; S4 immerses the shirt in the wear-resistant finishing liquid and pads it in a padding machine for 2-3 minutes, so that the finishing liquid can evenly penetrate into the fabric through the padding machine; S5 sends the impregnated shirt into a drying machine for baking; S6 performs static balancing on the baked shirts and then washes them to remove the residues on the surface of the fabrics; S7 dries the washed garments at a temperature of 60-90°C; S8 puts the dried garments into a cooling room for cooling to obtain wear-resistant shirts; The wear-resistant finishing liquid comprises the following raw materials in percentage by mass: 5-30% polyurethane wear-resistant agent, 0.5-3% penetrant JFC, 3-7% modified brucite powder, 1-5% modified sodium lignin sulfonate, 2-6% modified aerogel, and the balance is deionized water with an ion content of less than 20 ppm. The penetrant JFC is squeezed into the liquid, and its main component is fatty alcohol polyoxyethylene ether, which is a non-ionic surfactant with excellent wettability and re-wettability, thereby improving the permeability and uniformity of the wear-resistant agent in the shirt fabric.
[0005] Preferably, in step S5, the baking temperature is 140-160° C. and the baking time is 1-3 min.
[0006] Preferably, the polyurethane wear-resistant agent is prepared by polymerization of 2-ethyl-2-(hydroxymethyl)-1,3-propanediol and bis(isocyanatomethyl)benzene.
[0007] Preferably, the wear-resistant finishing liquid comprises the following raw materials in percentage by mass: 10-25% polyurethane wear-resistant agent, 1-2.5% penetrant JFC, 4-6% modified brucite powder, 2-4% modified sodium lignin sulfonate, 3-5% modified aerogel, and the balance is deionized water with an ion content of less than 20 ppm.
[0008] Preferably, the wear-resistant finishing liquid comprises the following raw materials in percentage by mass: 17.5% polyurethane wear-resistant agent, 1.75% penetrant JFC, 5% modified brucite powder, 3% modified sodium lignin sulfonate, 4% modified aerogel, and the balance is deionized water with an ion content of less than 20 ppm.
[0009] Preferably, the preparation method of the modified brucite powder is as follows: take 10-20 parts of brucite by weight, clean the surface, dry and perform preliminary crushing; then put it into a muffle furnace, roast it at 300-400°C for 1-2h, and grind it to a particle size of 400-500 mesh after cooling; then add 30-50ml of hypochlorous acid with a mass fraction of 5-10%, heat it in a water bath at 30-40°C and stir it thoroughly for 30-40min, and adjust the pH to 7.0; then add glycerol, heat it to 60-80°C, stir it for 1-2h, filter it to obtain a solid product, rinse it with deionized water 2-3 times, and then vacuum dry it at 80-100°C for 2-3h to obtain a solid powder, spread the solid powder 1-3mm in the constructed high-voltage electric field, and carry out Corona treatment for 30-40 minutes to obtain modified brucite powder; first calcination to remove water in different states in the structure, make the internal structure loose and porous, increase the specific surface area, then add hypochlorous acid, hypochlorous acid decomposes to produce oxygen and hydrochloric acid, soak in hydrochloric acid for surface corrosion modification to show porous characteristics, oxygen forms small bubbles and enters the interlayer of the structure to generate pressure, so that a larger space is generated inside the structure to improve adsorption, and then hydroxyl groups are introduced through propylene glycol modification, and the hydroxyl groups are combined with fabric fibers through multiple chemical bonds to improve the adhesion of brucite powder, improve the wear resistance and washability of the shirt, and finally, through corona treatment, the surface of brucite powder is made rougher, the specific surface area is increased, and it is more fully and tightly combined with the fabric fibers to form a stable wear-resistant layer to improve the wear resistance.
[0010] Preferably, the power supply frequency of the corona treatment is 20-25kHz, the working voltage is 30-40kV, and the discharge power is 90-100W.
[0011] Preferably, the preparation method of the modified sodium lignin sulfonate is as follows: 8-12 parts of sodium lignin sulfonate are taken by weight, heated and depolymerized at 150-160°C in 1 mol / L sodium hydroxide, and then separated and purified with ethanol, and then 1-2 parts of chloroacetic acid and 40-50 parts of deionized water are added, and the pH of the solution is adjusted to 10-11 with 25-35% sodium hydroxide aqueous solution, and the reaction time is stirred at 75-85°C for 1-2h, and finally 1-2 parts of ethanol solution of hexadecylamine with a concentration of 20-40% are added, and the stirring reaction is continued for 60-80min, and the obtained reaction solution is spray-dried to obtain modified sodium lignin sulfonate; first, carboxylate groups are introduced into the sodium lignin sulfonate by chloroacetic acid, which can combine with fabric fibers to form stable chemical bonds, thereby improving adhesion and washing resistance, and by adding hexadecylamine, a hydrophobic structure is introduced, and a hydrophobic film can be formed on the surface of the fabric fiber, reducing the erosion of water on the fabric fiber during washing, thereby improving washing resistance.
[0012] Preferably, the preparation method of the modified aerogel is as follows: 10-15 parts of silica aerogel by weight are put into a muffle furnace, oxygen is introduced at 200-300°C for 10-15 minutes, and after taking it out, it is mixed with 70-80 parts of polyethyleneimine and 30-40 parts of deionized water, stirred and reacted at 40-50°C for 40-50 minutes, and finally 3-5 parts of polyvinyl alcohol are added, and the stirring reaction is continued for 50-60 minutes, and the modified aerogel is obtained by vacuum drying, and oxygen is first introduced into the muffle furnace to graft hydroxyl groups on the surface of the silica aerogel to improve the reaction activity and enable chemical bonding with the fabric fiber, and then polyethyleneimine is added for infiltration to further improve the adsorption and adhesion properties of the silica aerogel, and the wear resistance and washing resistance are improved. Finally, polyvinyl alcohol is added, which has film-forming properties and helps to form a protective layer on the surface of the shirt fabric fiber to improve the wear resistance.
[0013] Compared with the prior art, the embodiments of the present application have the following beneficial effects: The preparation process of the wear-resistant shirt provided by the present invention is finished by a wear-resistant finishing liquid, so that the shirt fabric has excellent wear resistance, while maintaining the original comfort and air permeability of the fabric; by adding modified brucite powder to the wear-resistant finishing liquid, the wear resistance and wash resistance of the shirt are further improved, the specific surface area is increased, and the shirt is more fully and tightly combined with the fabric fiber to form a stable wear-resistant layer, and the wear resistance effect is improved; by adding modified sodium lignin sulfonate, the adhesion and wash resistance are improved, a hydrophobic film is formed on the surface of the fabric fiber, and the erosion of the fabric fiber by water during the washing process is reduced, thereby improving the wash resistance; by adding modified aerogel, the wear resistance and wash resistance are improved, and it is helpful to form a protective layer on the surface of the shirt fabric fiber to improve the wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The present invention is a schematic structural diagram of a process for preparing a wear-resistant shirt. DETAILED DESCRIPTION
[0015] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, not to describe a specific order.
[0016] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0017] Example 1 The embodiment of the present invention provides a preparation process of a wear-resistant shirt, such as Figure 1 As shown, the following steps are included: S1 selects shirt fabrics that are breathable and comfortable to wear, and pre-shrunk the fabrics; S2 performs cutting, piece inspection, gluing, sewing and ironing to produce finished shirts; S3 washes and pre-treats the shirts; S4 immerses the shirt in the wear-resistant finishing liquid and pads it in a padding machine for 2 minutes, so that the finishing liquid can evenly penetrate into the fabric through the padding machine; S5 sends the impregnated shirt into a drying machine for baking; S6 performs static balancing on the baked shirts and then washes them to remove the residues on the surface of the fabrics; S7 dries the washed garments at a temperature of 60°C; S8 puts the dried garments into a cooling room for cooling to obtain wear-resistant shirts; The wear-resistant finishing liquid comprises the following raw materials in percentage by mass: 5% polyurethane wear-resistant agent, 0.5% penetrant JFC, 3% modified brucite powder, 1% modified sodium lignin sulfonate, 2% modified aerogel, and the balance is deionized water with an ion content of less than 20 ppm.
[0018] Wherein, in step S5, the baking temperature is 140° C. and the baking time is 1 min.
[0019] In this embodiment, the polyurethane wear-resistant agent is prepared by polymerization of 2-ethyl-2-(hydroxymethyl)-1,3-propanediol and bis(isocyanatomethyl)benzene.
[0020] In a specific implementation, the preparation method of the modified brucite powder is as follows: take 10 parts of brucite by weight, clean the surface, dry and perform preliminary crushing; then put it into a muffle furnace, roast it at 300°C for 1h, and grind it to a particle size of 400 mesh after cooling; then add 30ml of hypochlorous acid with a mass fraction of 5%, heat it in a water bath at 30°C and stir it for 30min, and adjust the pH to 7.0; then add glycerol, heat it to 60°C, stir and react for 1h, filter and obtain a solid product, rinse it with deionized water twice, and then vacuum dry it at 80°C for 2h to obtain a solid powder, spread the solid powder 1mm in a constructed high-voltage electric field, and perform corona treatment for 30min to obtain a modified brucite powder.
[0021] Preferably, the power supply frequency of the corona treatment is 20kHz, the working voltage is 30kV, and the discharge power is 90W.
[0022] In this embodiment, the preparation method of the modified sodium lignin sulfonate is as follows: 8 parts of sodium lignin sulfonate are taken by weight, heated at 150°C in 1 mol / L sodium hydroxide for depolymerization, and then separated and purified with ethanol, and then 1 part of chloroacetic acid and 40 parts of deionized water are added, and the pH of the solution is adjusted to 10 with a 25% sodium hydroxide aqueous solution, and the reaction time is stirred at 75°C for 1h, and finally 1 part of 20% hexadecylamine ethanol solution is added, and the stirring reaction is continued for 60min, and the obtained reaction solution is spray-dried to obtain modified sodium lignin sulfonate.
[0023] In this embodiment, the preparation method of the modified aerogel is as follows: 10 parts of silica aerogel by weight are put into a muffle furnace, oxygen is introduced at 200° C. for 10 minutes, and then taken out and mixed with 70 parts of polyethyleneimine and 30 parts of deionized water, stirred and reacted at 40° C. for 40 minutes, and finally 3 parts of polyvinyl alcohol are added, and the stirring reaction is continued for 50 minutes, and the modified aerogel is obtained by vacuum drying.
[0024] Example 2 The embodiment of the present invention provides a preparation process of a wear-resistant shirt, such as Figure 1 As shown, the following steps are included: S1 selects shirt fabrics that are breathable and comfortable to wear, and pre-shrunk the fabrics; S2 performs cutting, piece inspection, gluing, sewing and ironing to produce finished shirts; S3 washes and pre-treats the shirts; S4 immerses the shirt in the wear-resistant finishing liquid and pads it in a padding machine for 2 minutes, so that the finishing liquid can evenly penetrate into the fabric through the padding machine; S5 sends the impregnated shirt into a drying machine for baking; S6 performs static balancing on the baked shirts and then washes them to remove the residues on the surface of the fabrics; S7 dries the washed garments at a temperature of 60°C; S8 puts the dried garments into a cooling room for cooling to obtain wear-resistant shirts; The wear-resistant finishing liquid includes the following raw materials in percentage by mass: 10% polyurethane wear-resistant agent, 1.5% penetrant JFC, 4% modified brucite powder, 2% modified sodium lignin sulfonate, 3% modified aerogel, and the balance is deionized water with an ion content of less than 20 ppm.
[0025] Wherein, in step S5, the baking temperature is 140° C. and the baking time is 1 min.
[0026] In this embodiment, the polyurethane wear-resistant agent is prepared by polymerization of 2-ethyl-2-(hydroxymethyl)-1,3-propanediol and bis(isocyanatomethyl)benzene.
[0027] In a specific implementation, the preparation method of the modified brucite powder is as follows: take 10 parts of brucite by weight, clean the surface, dry and perform preliminary crushing; then put it into a muffle furnace, roast it at 300°C for 1h, and grind it to a particle size of 400 mesh after cooling; then add 30ml of hypochlorous acid with a mass fraction of 5%, heat it in a water bath at 30°C and stir it for 30min, and adjust the pH to 7.0; then add glycerol, heat it to 60°C, stir and react for 1h, filter and obtain a solid product, rinse it with deionized water twice, and then vacuum dry it at 80°C for 2h to obtain a solid powder, spread the solid powder 1mm in a constructed high-voltage electric field, and perform corona treatment for 30min to obtain a modified brucite powder.
[0028] Preferably, the power supply frequency of the corona treatment is 20kHz, the working voltage is 30kV, and the discharge power is 90W.
[0029] In this embodiment, the preparation method of the modified sodium lignin sulfonate is as follows: 8 parts of sodium lignin sulfonate are taken by weight, heated at 150°C in 1 mol / L sodium hydroxide for depolymerization, and then separated and purified with ethanol, and then 1 part of chloroacetic acid and 40 parts of deionized water are added, and the pH of the solution is adjusted to 10 with a 25% sodium hydroxide aqueous solution, and the reaction time is stirred at 75°C for 1h, and finally 1 part of 20% hexadecylamine ethanol solution is added, and the stirring reaction is continued for 60min, and the obtained reaction solution is spray-dried to obtain modified sodium lignin sulfonate.
[0030] In this embodiment, the preparation method of the modified aerogel is as follows: 10 parts of silica aerogel by weight are put into a muffle furnace, oxygen is introduced at 200° C. for 10 minutes, and then taken out and mixed with 70 parts of polyethyleneimine and 30 parts of deionized water, stirred and reacted at 40° C. for 40 minutes, and finally 3 parts of polyvinyl alcohol are added, and the stirring reaction is continued for 50 minutes, and the modified aerogel is obtained by vacuum drying.
[0031] Example 3 The embodiment of the present invention provides a preparation process of a wear-resistant shirt, such as Figure 1 As shown, the following steps are included: S1 selects shirt fabrics that are breathable and comfortable to wear, and pre-shrunk the fabrics; S2 performs cutting, piece inspection, gluing, sewing and ironing to produce finished shirts; S3 washes and pre-treats the shirts; S4 immerses the shirt in the wear-resistant finishing liquid and pads it in a padding machine for 2.5 minutes, so that the finishing liquid can evenly penetrate into the fabric through the padding machine; S5 sends the impregnated shirt into a drying machine for baking; S6 performs static balancing on the baked shirts and then washes them to remove the residues on the surface of the fabrics; S7 dries the washed garments at a temperature of 75°C; S8 puts the dried garments into a cooling room for cooling to obtain wear-resistant shirts; The wear-resistant finishing liquid includes the following raw materials in percentage by mass: 17.5% polyurethane wear-resistant agent, 1.75% penetrant JFC, 5% modified brucite powder, 3% modified sodium lignin sulfonate, 4% modified aerogel, and the balance is deionized water with an ion content of less than 20 ppm.
[0032] Wherein, in step S5, the baking temperature is 150° C. and the baking time is 2 minutes.
[0033] In this embodiment, the polyurethane wear-resistant agent is prepared by polymerization of 2-ethyl-2-(hydroxymethyl)-1,3-propanediol and bis(isocyanatomethyl)benzene.
[0034] In a specific implementation, the preparation method of the modified brucite powder is as follows: 15 parts of brucite are taken by weight, the surface is cleaned, and preliminary crushing is performed after drying; then it is placed in a muffle furnace, roasted at 350° C. for 1.5 hours, and ground to a particle size of 450 mesh after cooling; then 40 ml of hypochlorous acid with a mass fraction of 7.5% is added, heated in a water bath at 35° C. and fully stirred for 35 minutes, and the pH is adjusted to 7.0; then glycerol is added, the temperature is raised to 70° C., and the reaction is stirred for 1.5 hours. After filtering, a solid product is obtained, which is rinsed with deionized water twice and then vacuum dried at 90° C. for 2.5 hours to obtain a solid powder, and the solid powder is spread 2 mm in a constructed high-voltage electric field, and corona treated for 35 minutes to obtain a modified brucite powder.
[0035] Preferably, the power supply frequency of the corona treatment is 22.5kHz, the working voltage is 35kV, and the discharge power is 95W.
[0036] In this embodiment, the preparation method of the modified sodium lignin sulfonate is as follows: 10 parts of sodium lignin sulfonate are taken by weight, heated at 155°C in 1 mol / L sodium hydroxide for depolymerization, and then separated and purified with ethanol, and then 1.5 parts of chloroacetic acid and 45 parts of deionized water are added, and the pH of the solution is adjusted to 10 with a 30% sodium hydroxide aqueous solution, and the reaction time is stirred at 80°C for 1.5 hours, and finally 1.5 parts of a 30% hexadecylamine ethanol solution is added, and the stirring reaction is continued for 70 minutes, and the obtained reaction solution is spray-dried to obtain modified sodium lignin sulfonate.
[0037] In this embodiment, the preparation method of the modified aerogel is as follows: 12.5 parts of silica aerogel are taken by weight and put into a muffle furnace, oxygen is introduced at 250° C. for 12.5 minutes, and then taken out and mixed with 75 parts of polyethyleneimine and 35 parts of deionized water, stirred and reacted at 45° C. for 45 minutes, and finally 4 parts of polyvinyl alcohol are added, and the stirring reaction is continued for 55 minutes, and the modified aerogel is obtained by vacuum drying.
[0038] Example 4 The embodiment of the present invention provides a preparation process of a wear-resistant shirt, such as Figure 1 As shown, the following steps are included: S1 selects shirt fabrics that are breathable and comfortable to wear, and pre-shrunk the fabrics; S2 performs cutting, piece inspection, gluing, sewing and ironing to produce finished shirts; S3 washes and pre-treats the shirts; S4 immerses the shirt in the wear-resistant finishing liquid and pads it in a padding machine for 3 minutes, so that the finishing liquid can evenly penetrate into the fabric through the padding machine; S5 sends the impregnated shirt into a drying machine for baking; S6 performs static balancing on the baked shirts and then washes them to remove the residues on the surface of the fabrics; S7 dries the washed garments at a temperature of 90°C; S8 puts the dried garments into a cooling room for cooling to obtain wear-resistant shirts; The wear-resistant finishing liquid includes the following raw materials in percentage by mass: 25% polyurethane wear-resistant agent, 2.5% penetrant JFC, 6% modified brucite powder, 4% modified sodium lignin sulfonate, 5% modified aerogel, and the balance is deionized water with an ion content of less than 20 ppm.
[0039] Wherein, in step S5, the baking temperature is 160° C. and the baking time is 3 minutes.
[0040] In this embodiment, the polyurethane wear-resistant agent is prepared by polymerization of 2-ethyl-2-(hydroxymethyl)-1,3-propanediol and bis(isocyanatomethyl)benzene.
[0041] In a specific implementation, the preparation method of the modified brucite powder is as follows: take 20 parts of brucite by weight, clean the surface, dry and perform preliminary crushing; then put it into a muffle furnace, roast it at 400°C for 2h, and grind it to a particle size of 500 mesh after cooling; then add 50ml of hypochlorous acid with a mass fraction of 10%, heat it in a water bath at 40°C and stir it for 40min, and adjust the pH to 7.0; then add glycerol, heat it to 80°C, stir and react for 2h, filter to obtain a solid product, rinse it with deionized water 3 times, and then vacuum dry it at 100°C for 3h to obtain a solid powder, spread the solid powder 3mm in a constructed high-voltage electric field, and perform corona treatment for 40min to obtain a modified brucite powder.
[0042] Preferably, the power supply frequency of the corona treatment is 25kHz, the working voltage is 40kV, and the discharge power is 100W.
[0043] In this embodiment, the preparation method of the modified sodium lignin sulfonate is as follows: 12 parts of sodium lignin sulfonate are taken by weight, heated at 160°C in 1 mol / L sodium hydroxide for depolymerization, and then separated and purified with ethanol, and then 2 parts of chloroacetic acid and 50 parts of deionized water are added, and the pH of the solution is adjusted to 11 with a 35% sodium hydroxide aqueous solution, and the reaction time is stirred at 85°C for 2 hours, and finally 2 parts of 40% hexadecylamine ethanol solution are added, and the stirring reaction is continued for 80 minutes, and the obtained reaction solution is spray-dried to obtain modified sodium lignin sulfonate.
[0044] In this embodiment, the preparation method of the modified aerogel is as follows: 15 parts of silica aerogel are taken by weight and put into a muffle furnace, oxygen is introduced at 300° C. for 15 minutes, taken out and mixed with 80 parts of polyethyleneimine and 40 parts of deionized water, stirred and reacted at 50° C. for 50 minutes, and finally 5 parts of polyvinyl alcohol are added, the stirring reaction is continued for 60 minutes, and vacuum drying is performed to obtain the modified aerogel.
[0045] Example 5 The embodiment of the present invention provides a preparation process of a wear-resistant shirt, such as Figure 1 As shown, the following steps are included: S1 selects shirt fabrics that are breathable and comfortable to wear, and pre-shrunk the fabrics; S2 performs cutting, piece inspection, gluing, sewing and ironing to produce finished shirts; S3 washes and pre-treats the shirts; S4 immerses the shirt in the wear-resistant finishing liquid and pads it in a padding machine for 3 minutes, so that the finishing liquid can evenly penetrate into the fabric through the padding machine; S5 sends the impregnated shirt into a drying machine for baking; S6 performs static balancing on the baked shirts and then washes them to remove the residues on the surface of the fabrics; S7 dries the washed garments at a temperature of 90°C; S8 puts the dried garments into a cooling room for cooling to obtain wear-resistant shirts; The wear-resistant finishing liquid includes the following raw materials in percentage by mass: 30% polyurethane wear-resistant agent, 0.3% penetrant JFC, 7% modified brucite powder, 5% modified sodium lignin sulfonate, 6% modified aerogel, and the balance is deionized water with an ion content of less than 20 ppm.
[0046] Wherein, in step S5, the baking temperature is 160° C. and the baking time is 3 minutes.
[0047] In this embodiment, the polyurethane wear-resistant agent is prepared by polymerization of 2-ethyl-2-(hydroxymethyl)-1,3-propanediol and bis(isocyanatomethyl)benzene.
[0048] In a specific implementation, the preparation method of the modified brucite powder is as follows: take 20 parts of brucite by weight, clean the surface, dry and perform preliminary crushing; then put it into a muffle furnace, roast it at 400°C for 2h, and grind it to a particle size of 500 mesh after cooling; then add 50ml of hypochlorous acid with a mass fraction of 10%, heat it in a water bath at 40°C and stir it for 40min, and adjust the pH to 7.0; then add glycerol, heat it to 80°C, stir and react for 2h, filter to obtain a solid product, rinse it with deionized water 3 times, and then vacuum dry it at 100°C for 3h to obtain a solid powder, spread the solid powder 3mm in a constructed high-voltage electric field, and perform corona treatment for 40min to obtain a modified brucite powder.
[0049] Preferably, the power supply frequency of the corona treatment is 25kHz, the working voltage is 40kV, and the discharge power is 100W.
[0050] In this embodiment, the preparation method of the modified sodium lignin sulfonate is as follows: 12 parts of sodium lignin sulfonate are taken by weight, heated at 160°C in 1 mol / L sodium hydroxide for depolymerization, and then separated and purified with ethanol, and then 2 parts of chloroacetic acid and 50 parts of deionized water are added, and the pH of the solution is adjusted to 11 with a 35% sodium hydroxide aqueous solution, and the reaction time is stirred at 85°C for 2 hours, and finally 2 parts of 40% hexadecylamine ethanol solution are added, and the stirring reaction is continued for 80 minutes, and the obtained reaction solution is spray-dried to obtain modified sodium lignin sulfonate.
[0051] In this embodiment, the preparation method of the modified aerogel is as follows: 15 parts of silica aerogel are taken by weight and put into a muffle furnace, oxygen is introduced at 300° C. for 15 minutes, taken out and mixed with 80 parts of polyethyleneimine and 40 parts of deionized water, stirred and reacted at 50° C. for 50 minutes, and finally 5 parts of polyvinyl alcohol are added, the stirring reaction is continued for 60 minutes, and vacuum drying is performed to obtain the modified aerogel.
[0052] Comparative Example 1 Compared with Example 3, the modified brucite powder is replaced by ordinary brucite powder.
[0053] Comparative Example 2 Compared with Example 3, the modified sodium lignin sulfonate is replaced by ordinary sodium lignin sulfonate.
[0054] Comparative Example 3 Compared with Example 3, the modified aerogel is replaced by ordinary aerogel.
[0055] Comparative Example 4 Compared with Example 3, the modified brucite powder is replaced by ordinary brucite powder, the modified sodium lignin sulfonate is replaced by ordinary sodium lignin sulfonate, and the modified aerogel is replaced by ordinary aerogel.
[0056] Comparative Example 5 A commercially available wear-resistant shirt.
[0057] Clothing testing The shirts of Examples 1-5 and Comparative Examples 1-5 were subjected to wear resistance tests and air permeability tests. The test results are shown in Table 1 below: Group Abrasion resistance before washing (transfer) Abrasion resistance after 50 washes (transfer) Air permeability (mm / s) Example 1 3081 2908 455 Example 2 3085 2911 457 Example 3 3089 2915 461 Example 4 3086 2913 459 Example 5 3083 2910 456 Comparative Example 1 2428 2224 455 Comparative Example 2 2489 2236 457 Comparative Example 3 2435 2201 455 Comparative Example 4 1655 1405 459 Comparative Example 5 996 653 424 From the above results, it can be seen that the shirt prepared by the present invention has good wear resistance and air permeability, especially by adding modified brucite powder, modified sodium lignin sulfonate and modified aerogel, the three have a synergistic effect, and the wear resistance is further improved.
[0058] It should be noted that, for the above embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the described order of actions, because according to the present invention, some steps may be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and modules involved are not necessarily required by the present invention.
[0059] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the scope of protection of the invention. Obviously, the described embodiments are only some embodiments of the present invention, rather than all embodiments. Based on these embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in this field can still combine, add, delete or make other adjustments to the features in the various embodiments of the present invention according to the circumstances without conflict, without making creative work, so as to obtain different other technical solutions that do not deviate from the concept of the present invention in essence, and these technical solutions also belong to the scope of protection of the present invention.
Claims
1. A process for preparing a wear-resistant shirt, characterized in that: The steps include: S1 selects shirt fabrics that are breathable and comfortable to wear, and pre-shrunk the fabrics; S2 performs cutting, piece inspection, gluing, sewing and ironing to produce finished shirts; S3 washes and pre-treats the shirts; S4 immerses the shirt in the wear-resistant finishing liquid and pads it in a padding machine for 2-3 minutes, so that the finishing liquid can evenly penetrate into the fabric through the padding machine; S5 sends the impregnated shirt into a drying machine for baking; S6 performs static balancing on the baked shirts and then washes them to remove the residues on the surface of the fabrics; S7 dries the washed garments at a temperature of 60-90°C; S8 puts the dried garments into a cooling room for cooling to obtain wear-resistant shirts; The wear-resistant finishing liquid comprises the following raw materials in percentage by mass: 5-30% polyurethane wear-resistant agent, 0.5-3% penetrant JFC, 3-7% modified brucite powder, 1-5% modified sodium lignin sulfonate, 2-6% modified aerogel, and the balance is deionized water with an ion content of less than 20 ppm.
2. The process for preparing the wear-resistant shirt according to claim 1, characterized in that: In step S5, the baking temperature is 140-160° C. and the baking time is 1-3 minutes.
3. The process for preparing the wear-resistant shirt according to claim 1, characterized in that: The polyurethane wear-resistant agent is prepared by polymerization of 2-ethyl-2-(hydroxymethyl)-1,3-propylene glycol and bis(isocyanatomethyl)benzene.
4. The process for preparing the wear-resistant shirt according to claim 1, characterized in that: The wear-resistant finishing liquid comprises the following raw materials in percentage by mass: 10-25% polyurethane wear-resistant agent, 1-2.5% penetrant JFC, 4-6% modified brucite powder, 2-4% modified sodium lignin sulfonate, 3-5% modified aerogel, and the balance is deionized water with an ion content of less than 20 ppm.
5. The process for preparing the wear-resistant shirt according to claim 4, characterized in that: The wear-resistant finishing liquid includes the following raw materials in percentage by mass: 17.5% polyurethane wear-resistant agent, 1.75% penetrant JFC, 5% modified brucite powder, 3% modified sodium lignin sulfonate, 4% modified aerogel, and the balance is deionized water with an ion content of less than 20 ppm.
6. The process for preparing the wear-resistant shirt according to claim 1, characterized in that: The preparation method of the modified brucite powder is as follows: taking 10-20 parts of brucite by weight, cleaning the surface, drying and performing preliminary crushing; then putting it into a muffle furnace, roasting it at 300-400° C. for 1-2 hours, and grinding it to a particle size of 400-500 mesh after cooling; then adding 30-50 ml of hypochlorous acid with a mass fraction of 5-10%, heating it in a water bath at 30-40° C. and fully stirring it for 30-40 minutes, and adjusting the pH to 7.0; then adding glycerol, heating it to 60-80° C., stirring and reacting it for 1-2 hours, filtering to obtain a solid product, washing it with deionized water 2-3 times, and vacuum drying it at 80-100° C. for 2-3 hours to obtain a solid powder, spreading the solid powder 1-3 mm in a constructed high-voltage electric field, and performing corona treatment for 30-40 minutes to obtain a modified brucite powder.
7. The process for preparing the wear-resistant shirt according to claim 6, characterized in that: The power supply frequency of the corona treatment is 20-25kHz, the working voltage is 30-40kV, and the discharge power is 90-100W.
8. The process for preparing the wear-resistant shirt according to claim 1, characterized in that: The preparation method of the modified sodium lignin sulfonate is as follows: taking 8-12 parts of sodium lignin sulfonate by weight, heating and depolymerizing in 1 mol / L sodium hydroxide at 150-160° C., then separating and purifying with ethanol, then adding 1-2 parts of chloroacetic acid and 40-50 parts of deionized water, adjusting the pH of the solution to 10-11 with a 25-35% sodium hydroxide aqueous solution, stirring and reacting at 75-85° C. for 1-2 hours, finally adding 1-2 parts of an ethanol solution of hexadecylamine with a concentration of 20-40%, continuing to stir and react for 60-80 minutes, and spray drying the obtained reaction solution to prepare the modified sodium lignin sulfonate.
9. The process for preparing the wear-resistant shirt according to claim 6, characterized in that: The preparation method of the modified aerogel is as follows: 10-15 parts of silica aerogel by weight are put into a muffle furnace, oxygen is introduced at 200-300° C. for 10-15 minutes, taken out and mixed with 70-80 parts of polyethyleneimine and 30-40 parts of deionized water, stirred and reacted at 40-50° C. for 40-50 minutes, and finally 3-5 parts of polyvinyl alcohol are added, the stirring reaction is continued for 50-60 minutes, and vacuum drying is performed to obtain the modified aerogel.